2012
DOI: 10.1002/eji.201141765
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent effects of dendritic cells displaying prostaglandin E2‐induced indoleamine 2,3‐dioxygenase

Abstract: Prostaglandin E2 (PGE 2 ), an abundantly produced lipid messenger in mammalian organisms, has been attributed to possess potent albeit ambivalent immunological functions. Recently, PGE 2 has been reported to stimulate the commonly believed immunosuppressive indoleamine 2,3-dioxygenase (IDO) pathway in human dendritic cells (DCs), but without promoting DC immunosuppressive activity. Here, we report that PGE 2 used as a DC maturation agent apparently has more diverse functions. PGE 2 -matured DCs acquired powerf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
(141 reference statements)
0
20
0
Order By: Relevance
“…2C). PGE 2 was reported to promote immune tolerance by regulating IDO expression (36,37). To corroborate whether COXderived PGE 2 acts as another potential humoral factor, we incubated MSC-treated PBMCs in the MLR with IDM, a nonselective COX inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…2C). PGE 2 was reported to promote immune tolerance by regulating IDO expression (36,37). To corroborate whether COXderived PGE 2 acts as another potential humoral factor, we incubated MSC-treated PBMCs in the MLR with IDM, a nonselective COX inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Dead cells were removed after incubation at 37°C for 1.5 h, while living cells were differentiated with 1000 U/ml GM-CSF and 400 U/ml IL-4. Medium including cytokines was replaced on day 3 and iDCs were harvested on day 5 (Lanzinger et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Human PBMCs were separated from whole blood by density centrifugation (Lanzinger et al, 2012). PBMCs were cultured in RPMI-1640 medium supplemented with GlutaMAX–I (Gibco) and 2% human plasma (OP, Octapharma).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to these findings, it was reported that the induction of IDO expression by PGE2 occurs through its receptor EP4 instead of EP2 and that PGE2-matured DCs were more capable of inducing both allogeneic and Ag-specific T cell proliferation when compared to DCs matured in the absence of this molecule (Krause et al 2007). More recently (Lanzinger et al 2012), it was shown that the stimulatory effect of PGE2-matured DCs on allogeneic T cells is variable and may be highly context dependent. When the IDO activity in the microenvironment is low, DCs act as effective stimulators of immune responses; however, once the enzymatic activity of IDO predominates, these cells suppress T cell responsiveness and/or promote regulatory T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that VEGF causes defective DC differentiation and maturation (Gabrilovich et al 1998, Menetrier-Caux et al 1998, Oyama et al 1998, Zhang et al 2003, Takahashi et al 2004). Moreover, the addition of VEGF to DC cultures promotes a weak stimulus for Ag-specific T cells due to an inhibitory effect mediated by VEGF receptor 1 (VEGFR1)/Flt-1 signalling (Nemeth et al 2004, Laxmanan et al 2005). Of the described receptors for VEGF, VEGFR1 is the primary mediator of DC maturation inhibition (Dikov et al 2005), whereas VEGFR2 is responsible for signal transduction in mature DCs, activating extracellular signal-regulated protein kinases 1 and 2 and impairing the DC stimulation of allogeneic lymphocytes (Kadambi et al 2001, Mimura et al 2007).…”
mentioning
confidence: 99%